Round-Number Effects in Real Estate Prices: Evidence from Germany - Florian Englmaier; Andreas Roider; Lars Schlereth; Steffen Sebastian (Center for Economic Studies and ifo Institute (CESifo), 2023)
Round numbers affect behavior in various domains, e.g., as prominent thresholds or focal points in bargaining. In line with earlier findings, residential real estate transactions in Germany cluster at round-number prices, but there are also interesting (presumably cultural) differences. We extend our analysis to the commercial real estate market, where stakes are even higher and market participants arguably more experienced. For the same type of object, professionals cluster significantly less on round-number prices compared to non-professionals. We employ machine learning and show that transactions of family homes and condominiums at round-number prices are 2–7% above their hedonic values.
Keywords: D01; D91; C78; R31; 330; round-number effects; focal points; residential real estate; commercial real estate; housing prices; machine learning